2010
DOI: 10.1111/j.1472-765x.2010.02829.x
|View full text |Cite
|
Sign up to set email alerts
|

Competitive exclusion as a mode of action of a novel Bacillus cereus aquaculture biological agent

Abstract: Aims:  To determine the contribution of potential modes of action of a Bacillus cereus aquaculture biological control agent in inhibition of the fish pathogen, Aeromonas hydrophila. Methods and Results:  When B. cereus was tested in plate well inhibition studies, no production of antimicrobial compounds was detected. Bacillus cereus had a high growth rate (0·96 h−1), whereas Aer. hydrophila concentration decreased by c. 70% in co‐culture experiments. In nutrient limitation studies, B. cereus had a significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 36 publications
0
30
0
Order By: Relevance
“…Nonetheless, it could be hypothesized from the present investigation that the extracellular enzyme-producing bacteria colonizing within the GI tract of Catla catla might offer protection against the pathogenic Aeromonas strains. Although, the mechanism of inhibition was not characterized here, preceding studies suggested that the growth of pathogens (e.g., A. hydrophila) might be inhibited by competitive exclusion, competition for essential nutrients (e.g., glucose and iron) and siderophore production (Lalloo et al 2010). The method used in the presently reported study to assay the antagonistic effect of the putative probiotics (agar-overlay/double-layer) demonstrates the infl uence of diffusing antimicrobial products on growth of the pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, it could be hypothesized from the present investigation that the extracellular enzyme-producing bacteria colonizing within the GI tract of Catla catla might offer protection against the pathogenic Aeromonas strains. Although, the mechanism of inhibition was not characterized here, preceding studies suggested that the growth of pathogens (e.g., A. hydrophila) might be inhibited by competitive exclusion, competition for essential nutrients (e.g., glucose and iron) and siderophore production (Lalloo et al 2010). The method used in the presently reported study to assay the antagonistic effect of the putative probiotics (agar-overlay/double-layer) demonstrates the infl uence of diffusing antimicrobial products on growth of the pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, pathogen inhibitory potential of the bacilli has been rarely indicated. B. subtilis SG4 isolated from the gut of mrigal, C. mrigala (see Ghosh et al 2007), B. methylotrophicus isolated from channel catfi sh intestine (Ran et al 2012), and B. cereus and B. circulans isolated from the gut of some other fi sh species (Lalloo et al 2010, Geraylou et al 2014) were reported to be antagonistic against different strains of A. hydrophila. In addition, enzyme-producing B. thuringiensis isolated from the GI tract of the Atlantic salmon, Salmo salar Linnaeus, 1758, was shown to inhibit A. salmonicida subsp.…”
Section: Discussionmentioning
confidence: 99%
“…strain NM 12 produces siderophores with a wide antibacterial spectrum that inhibited the growth of 62.5% of 363 intestinal bacteria identified from several coastal fishes (Li and Chi, 2004). In addition, siderophores produced by Bacillus cereus has also been found to inhibit the growth of the fish pathogen Aeromonas hydrophila (Lalloo et al, 2010). Recently it was found that several siderophore-producing bacteria isolated from the intestinal tracts of fishes inhibit fish pathogens such as Aliivibrio logei, Vibrio ichthyoenteri, V. anguillarum, Vibrio splendidus and A. salmonicida (Sugita et al, 2012).…”
Section: Biocontrol Of Fish Pathogensmentioning
confidence: 99%
“…It is well known that the gastrointestinal microbiota of aquatic animals can be modified, for example, by ingestion of other microorganism; therefore, microbial manipulation constitutes a viable tool to reduce or eliminate the incidence of opportunistic pathogen (Balcazar, 2002). The direct effect, such as inhibiting the growth of other microorganisms, might be the main action that can occur in cultured systems (Kesarcodi-Watson et al, 2008;Jiang et al, 2013;Giri et al, 2013), and studies have illustrated that indigenous microorganisms have great potential because of the higher probability of competitive exclusion due to adaptation to the same ecological niche (Lalloo et al, 2010). Adhesion and colonization on the mucosal surfaces are possible protective mechanisms against pathogens through competition for binding sites and nutrients (Salyers and White, 2002).…”
Section: Competitive Inhibition Of Pathogenic Bacteriamentioning
confidence: 99%